The systematics of the Mongolepidida (Chondrichthyes) and the Ordovician origins of the clade - Plamen Andreev; Michael I. Coates; Valentina Karatajūtė-Talimaa; Richard M. Shelton; Paul R. Cooper; Nian-Zhong Wang; Ivan J. Sansom (PeerJ, 2016)
The Mongolepidida is an Order of putative early chondrichthyan fish, originally erected to unite taxa from the Lower Silurian of Mongolia. The present study reassesses mongolepid systematics through the examination of the developmental, histological and morphological characteristics of scale-based specimens from the Upper Ordovician Harding Sandstone (Colorado, USA) and the Upper Llandovery–Lower Wenlock Yimugantawu (Tarim Basin, China), Xiushan (Guizhou Province, China) and Chargat (north-western Mongolia) Formations. The inclusion of the Mongolepidida within the Class Chondrichthyes is supported on the basis of a suite of scale attributes (areal odontode deposition, linear odontocomplex structure and lack of enamel, cancellous bone and hard-tissue resorption) shared with traditionally recognized chondrichthyans (euchondrichthyans, e.g., ctenacanthiforms). The mongolepid dermal skeleton exhibits a rare type of atubular dentine (lamellin) that is regarded as one of the diagnostic features of the Order within crown gnathostomes. The previously erected Mongolepididae and Shiqianolepidae families are revised, differentiated by scale-base histology and expanded to include the genera Rongolepisand Xinjiangichthys, respectively. A newly described mongolepid species (Solinalepis levis gen. et sp. nov.) from the Ordovician of North America is treated as family incertae sedis, as it possesses a type of basal bone tissue (acellular and vascular) that has yet to be documented in other mongolepids. This study extends the stratigraphic and palaeogeographic range of Mongolepidida and adds further evidence for an early diversification of the Chondrichthyes in the Ordovician Period, 50 million years prior to the first recorded appearance of euchondrichthyan teeth in the Lower Devonian.